Perbandingan Hukum Terkait Peraturan Pengelolaan Sampah di Indonesia dan Korea Selatan - Agustianto, Agustianto; Fitri, Winda; Siregar, Abigael Hosanna (University of Merdeka Malang, 2023)
The writing of this scientific work was written because of the increasing environmental damage due to waste disposal carried out by individuals and groups without paying attention to the consequences for the environment, to raise awareness to the public about the obligation to dispose of waste in its place and be responsible for it by not littering, this research uses normative legal research methods the author takes studies from previous authors, as well as literacy literature and laws. The new thing found in this research is that South Korea as a country is more assertive in addressing the disposal and processing of waste in its country by making special regulations where it is mandatory to sort and dispose of waste in plastic that is specific to the type of waste disposed of. The regulation of waste disposal and processing in Indonesia is still not well implemented by the community with the lack of strict action against violators increasing, considering that Indonesia is still a developing country and South Korea is a developed country which is one of the distinguishing factors in this case, it is good that Indonesia can start imitating and slowly moving in order to reduce environmental damage that occurs due to disposal of garbage that is not in its place.